Analysis of knee joint movement when using alpine skis of different widths and related risk factors for injury - Zorko, M.; Lešnik, B.; Kolman, K.; Supej, M. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The aim of the study was to establish differences in positions of the knee joint of competitive skiers during a ski turn using skis of different widths.